2006
DOI: 10.1111/j.1432-2277.2006.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pancreas transplantation for life-threatening allergy to human insulin*

Abstract: Summary We report on a 30‐year‐old man, with type 1 diabetes mellitus, who developed generalized allergy to insulin consisting of several bouts of tremor, tachycardia, breathlessness and syncope. Strong positive reactions to protamine and metacresol were demonstrated by skin‐prick testing. Symptoms persisted despite the use of antihistamine therapy, Actrapid HM Paraben® and Monotard® (insulin without protamine and metacresol) and immunosuppression (tacrolimus). He underwent a cadaver pancreas transplantation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Tacrolimus aiming for serum trough levels between 5 and 10 ng/ml was given to a patient with generalized insulin allergy; however no improvement of his symptomatology was observed [65]. In a very recent paper, Yong et al [66] reported a patient with severe generalized insulin allergy who was treated successfully by the sequential use of two targeted biologic agents, rituximab and omalizumab, in a two-step therapeutic approach which also consisted of the use of prednisolone and mycophenolate mofetil.…”
Section: Other Treatment Optionsmentioning
confidence: 98%
“…Tacrolimus aiming for serum trough levels between 5 and 10 ng/ml was given to a patient with generalized insulin allergy; however no improvement of his symptomatology was observed [65]. In a very recent paper, Yong et al [66] reported a patient with severe generalized insulin allergy who was treated successfully by the sequential use of two targeted biologic agents, rituximab and omalizumab, in a two-step therapeutic approach which also consisted of the use of prednisolone and mycophenolate mofetil.…”
Section: Other Treatment Optionsmentioning
confidence: 98%
“…Pancreas transplantation would theoretically eliminate the need for subcutaneous insulin; however, this entails significant surgical risks and long-term immunosuppression that must be considered. 16,17 Intraperitoneal administration of insulin via continuous intraperitoneal insulin infusion (CIPII) with an implantable insulin pump has been studied to improve glycemic control in patients with type 1 diabetes mellitus for whom other therapies have failed, although this treatment is neither cost effective nor widely available. 18 Lastly, inhaled insulin would appear to be an attractive option for patients with cutaneous hypersensitivity reactions to insulin, although to our knowledge no data exist evaluating its use in such patients, and it can currently be found only as a short-acting formulation.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with definitive therapy, non-specific treatments such as anti-histamines and immunosuppressants [25] may be required. In some very severe cases of allergy, extreme measures have been resorted to, including the use of biologic agents (rituximab and omalizumab) [28] and even pancreatic transplant [29].…”
Section: Discussionmentioning
confidence: 99%